Animal models in antihypertensive drug development research - Dwi Aris Agung Nugrahaningsih; Mia Munawarroh Yuniyanti; Rahmi Ayu Wijayaningsih; Mosa Rini Nurul Hidayati; Setyo Purwono (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2020)
Hypertension is one of the most common diseases in the world. However, its pathogenesis is not fully understood and its treatment is not yet satisfying. Animal models of hypertension have been useful to understand the pathogenesis of hypertension and to test novel therapeutic agents. There are several kinds of hypertension animal models. Each model has different characteristics. Knowing the characteristic of each model is important to obtain valid research. This review will describe several available methods to develop animal model for hypertension.